NATO's new strategic concept - A test for Transatlantic relations; Noul concept strategic al NATO - Un test pentru relaţiile Transatlantice - Agnes Nicolescu (European Institute of Romania, 2010)
In order for NATO to remain credible and efficient, its new Strategic Concept must address and find solutions to fundamental issues which are likely to define the Alliance's missions over the next decade, of which the most important ones concern member states' ability to ensure and reinforce their mutual defense and burden-sharing commitments. The challenge of NATO's new Strategic Concept is to strike a balance between the objectives of deterrence and defense, and stronger security guarantees for member states, on the one hand, as well as greater reassurance to Russia, on the other hand. The document expected to be adopted by NATO member states at the Lisbon Summit should aim at building greater internal commitment and mutual confidence, while identifying more venues of political cooperation with Russia, even outside the NATO-Russia Council. The paper looks closely at those factors which influence the options made by allies when dealing with topics like forward defense, nuclear deterrence and strategic reassurance. The Alliance's new strategic concept is likely to acknowledge the danger posed by unconventional security threats but there are little chances for article 5 of the Washington Treaty to suffer major alterations, although the scope of potential threats has broadened. NATO's nuclear posture will continue to remain strongly linked to that of the United States, while Allies take note of the rising profile of other major nuclear powers on the international scene, the most prominent one being China.
Keywords: 330; nuclear deterrence; de-alerting of nuclear weapons; forward defense; strategic assurance; mutual assured destruction; contingency planning; Internationale Sicherheit; Strategie; Militärbündnis; NATO-Staaten